Beta defensin-1 gene polymorphisms and susceptibility to atypical squamous cells of undetermined significance lesions in Italian gynecological patients. - Casalicchio, Giorgia; Freato, Nadia; Maestri, Iva; Comar, Manola; Crovella, Sergio; Segat, Ludovica (J Med Virol, 2014)
The role of the human beta-defensin 1 (hBD-1) in the susceptibility to the onset of the Atypical Squamous Cells of Undetermined Significance (ASCUS) lesion, in the presence or not of HPV infection, is still unknown. In the current study, the three functional single nucleotide polymorphisms (SNPs) -52G > A, -44C > G, and -20G > A at the 5' un-translated region (UTR) of DEFB1 gene, encoding hBD-1, were analyzed in ASCUS lesion gynecological patients and healthy women from the north-east of Italy (Trieste). Cervical samples from 249 European-Caucasian women were collected, screened for HPV and cytologically evaluated; DEFB1 genotyping has been performed by direct sequencing. No significant differences were found for -52G > A, -44C > G, and -20G > A SNPs allele and genotype frequencies between women with and without ASCUS lesions. DEFB1 minor haplotypes were significantly more frequent in ASCUS lesion positive than negative women, associating with an increased risk of this type of lesion. When women were stratified according to HPV infection status, significant differences in the distribution of -52G > A SNP genotype frequencies were found: the presence of the A allele in the homozygous genotype A/A associated with a lower risk of developing ASCUS lesions in HPV negative women. DEFB1 minor haplotypes were also associated with an increased risk of developing ASCUS lesions, being significantly more frequent in HPV negative women with lesions, than without lesions. Although these results highlight the possible involvement of DEFB1, further studies are needed to support the role of DEFB1 in the modulation of the susceptibility to ASCUS lesions.
Keywords: 5' Untranslated Regions; Adolescent; Adult; Atypical Squamous Cells of the Cervix; beta-Defensins; Female; Genotype; Humans; Italy; Papillomavirus Infections; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Uterine Cervical Neoplasms; Young Adult